Learning English through Own Context Creation - Pylynskyi, Mykhailo (Educological discourse, 2023)
The article offers a method of teaching English, according to which teaching is conducted exclusively in English through interpretation. The method is opposed to the more usual method in which the teacher and students use Ukrainian translation. According to the author, the method proposed in the article is more productive, because it is aimed at the development of memory and thinking in students. This process occurs by creating one’s own contexts for unfamiliar vocabulary instead of the commonly used methods of filling in a blank in a sentence, matching, or translating. The article contains a detailed description and comparison of the theoretical part of both methods and features of their practical application. First, the author in the article outlines the terminology that will be used in the article and indicates the broader context of the application of the proposed method with any pair of languages. Next, the author of the article cites the advantages of the interpretive method and outlines its shortcomings, comparing it with the translation method. Among the advantages, the author cites the improvement of the quality of oral and written communication by developing the skill of understanding the interlocutor without translation, posing questions about the misheard and unknown vocabulary in a polite way, and searching for the necessary information. Also, the advantage of the interpretive method is that access to information is significantly expanded in this way, as well as the accuracy of the use of vocabulary increases, taking into account the language situation and the personality of the speaker. Among the shortcomings, the author cites various inaccuracies of the dictionaries, and the need for a highly educated teacher to use this method. Then the article presents commonly used exercises aimed at learning and checking the learned vocabulary. The author outlines the shortcomings of these exercises and instead offers his own exercise, which is subject to the interpretative method of teaching English. Among the shortcomings, the author cites the students’ desire to cheat by guessing the correct answer, the rigidity of the given context and the difficulty of independent use of the learned vocabulary outside this context, the increase in the gap between students with different levels of English proficiency.